Petroleum Engineering in Oil and Gas Production: Advances in Theory and Operation - Xu, Xingguang; Xie, Kun; Yang, Yang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Reprint presents the latest progress in the theory and operation of oil and gas production, especially the advances in the development of unconventional reservoirs and harsh-condition reservoirs. It can be used as a reference for those work in related or relevant areas.